Effect of Hydrogen Peroxide on Physicochemical Properties of Common Konjac (Amorphophallus oncophyllus) Flour by Maceration and Ultrasonic Methods - Widjanarko, Simon Bambang; Sutrisno, Aji; Faridah, Anni (Jurnal Teknologi Pertanian, 2011)
Common konjac flour (CKF) from Indonesia has dark brown in color and itching property that considered unsuitable for human consumption due to the high presence of calcium oxalate. Therefore it needs purification.Â  The objective of this research is to reduce the amount of calcium oxalate as well as to increase its glucomannan content, viscosity, beside to produce white CKF. CKF was extracted by maceration method for 4 hours with 40% ethanol solution containing hydrogen peroxide. This extraction process was repeated at 60% ethanol solution, as well as at 80% ethanol solution. Hydrogen peroxide concentrations used in this experiment were 0.5, 1, 1.5, 2, 2.5, and 3%.Â  â€œBath typeâ€ ultrasonic was used to purify CKF for 15 minutes. The extraction process was similar to the above maceration method. The results showed that both maceration and ultrasonic extraction methods increased the degree of whiteness, glucomannan, and viscosity, in fact reduced the amount of calcium oxalate content. Conclusion of this experiment was that both extraction methods (maceration and ultrasonic) were achieved, whenÂ  CKF was washed in three levels ofÂ  ethanol solution, whichÂ  were at 40 %, followed by 60% andÂ  80% ethanolÂ  solutionsÂ  containingÂ  0.5% hydrogen peroxide, in each stage of purification process.Â  The least hydrogen peroxide residue in CKF was shown by treating CKF in three levels of ethanol solution containing 0.5% Â H2 O 2Â  which was 123.24 ppm. Keywords: common konjac flour, multistage ethanol washing, maceration, ultrasonic, hydrogen peroxide